REENGINEERING ORGANIZAȚIONAL CA OPORTUNITATE DE DEZVOLTARE A AFACERILOR - Prodan-Şestacova, Liubovi; Frunză, Octavian (CEP USM, 2024)
The business environment is becoming more and more competitive, the transformations and possibilities of modern technologies increasingly lead to the realization of a business in a constrained, economic, social, ecological paradigm, which exploits less resources (human, natural and energetic). All these objectives can be oﬀset by a rational, thoughtful, economical, responsible and technological business approach. In this way, contemporary business exposes itself to a continuous revision of the way of doing things through reengineering of organizational infrastructure and processes where gaps, discrepancies, ineﬃciencies and organizational losses are hidden. Through a correct and rational modeling of contemporary organizations, one can extract unexpected dividends and exponential gains from existing businesses, gain competitive position in the market and at the same time comply with social and ecological standards, rules and requirements.
ORGANIZATIONAL REENGINEERING AS AN OPPORTUNITY FOR BUSINESS DEVELOPMENT
Keywords: business process; change; reengineering; strategy